2022
DOI: 10.1111/jfbc.14287
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on blood pressure and skin using roselle drink: A clinical trial

Abstract: Roselle (Hibiscus sabdariffa L.) is an increasingly attractive plant for its health and pharmaceutical, beverage, and cosmetic applications. The purpose of this study was to investigate the clinical effects of roselle drink on antioxidant activity, blood pressure, and skin condition. Roselle drink used in this study contained rich phenolics (1.96 g of gallic acid equivalent/100 ml) and anthocyanins (1.65 g of cyanidin‐3‐glucoside equivalent/100 ml). In a randomized, cross‐over, double‐blind, placebo‐controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…[5][6][7] Previous studies showed that H. sabdariffa contains anthocyanins, flavonoids, phenolic compounds, glycosides, tannins, alkaloids, terpenoids, vitamin C, and organic acids, [8][9][10] which can be useful as antioxidants, 11,12 antibacterials, 9 antidiabetics, 13 anti-inflammatory agents and immunomodulators, 14 and anticancer agents. 15 Previous research also showed that H. sabdariffa helps lower cholesterol levels, 16,17 reduce obesity, 18 lower blood pressure, [19][20][21][22] and improve kidney function in people with hypertension. 24,25 and is rich in cucurbitacins (terpenoids), 26,27 which can be useful as antibacterial and anticancer, 28 anti-inflammatory, 29,30 and antihypertensive agents, 7 as well as helping wound healing, 31 and reducing pain in osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Previous studies showed that H. sabdariffa contains anthocyanins, flavonoids, phenolic compounds, glycosides, tannins, alkaloids, terpenoids, vitamin C, and organic acids, [8][9][10] which can be useful as antioxidants, 11,12 antibacterials, 9 antidiabetics, 13 anti-inflammatory agents and immunomodulators, 14 and anticancer agents. 15 Previous research also showed that H. sabdariffa helps lower cholesterol levels, 16,17 reduce obesity, 18 lower blood pressure, [19][20][21][22] and improve kidney function in people with hypertension. 24,25 and is rich in cucurbitacins (terpenoids), 26,27 which can be useful as antibacterial and anticancer, 28 anti-inflammatory, 29,30 and antihypertensive agents, 7 as well as helping wound healing, 31 and reducing pain in osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…To date, non-steroidal anti-inflammatory agents and diseasemodifying anti-rheumatic drugs, like immunosuppressants and monoclonal antibodies (e.g., rituximab and tocilizumab) combined with methotrexate, have been largely used to attenuate RA; however, most of them are expensive, rarely effective or tolerable, and lead to several unwanted effects, including allergy and infections, gastrointestinal problems, fluid retention, renal dysfunction and systemic vasculitis, cytopenia, lymphopenia, neutropenia, and the elevation of transaminase and cholesterol [7][8][9][10][11][12][13]. Among the new and most promising availability strategies, special attention has been given to bioactive molecules largely found in nature, namely, polyphenols, since their chemical structure with catechol methoxy and pyrogallol groups confer them notable health benefits, like antioxidant, anti-inflammatory, anti-bacterial, and antiproliferative activities, as well as the capacity to prevent neurological and cardiovascular pathologies, promote gastrointestinal health and vision without, it is believed, side-effects, and enhance wound healing [14][15][16][17][18][19][20][21][22][23]. In addition, polyphenols are also easier to obtain, water-soluble, and more economical than chemical drugs, and have already shown effectiveness in inhibiting JAK proteins and JAK/STAT signaling pathways [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It contains anthocyanins, organic acids, and ascorbic acid (40, 41). Its phytoconstituents have been found to have anti-diarrheal, antispasmodic, anti-hypertensive, and anti-inflammatory activities (39,(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%